Appendiceal Mucocele Presenting as a Right Adnexal Mass: A Case Report. (13th September 2010) - Gortchev, Grigor; Tomov, Slavcho; Dimitrov, Dobromir; Nanev, Vasil; Betova, Tatyana
Abstract : A 68-year-old female presented to the Gynecologic Oncology Clinic with a right-lower quadrant abdominal mass 3 × 4 cm in diameter palpable on pelvic examination. Her routine laboratory tests were normal. Transvaginal ultrasonography revealed a cystic mass in the right adnexa 3.9 cm in diameter, which was thought to arise in the ovary. At the time of laparoscopy, a 3 × 4 cm tumor arising from the distal end of the appendix was noted. A laparoscopic appendectomy with tumor removal was performed. Histologic examination of the surgical specimen revealed a mucocele of the appendix (AM). Although rare, this tumor should be considered in the differential diagnosis of a right adnexal mass. These tumors can be identified laparoscopically and removed by minimally invasive surgery.